RANCANG BANGUN SISTEM INFORMASI “OBATPEDIA” SEBAGAI MEDIA EDUKASI TENTANG OBAT-OBATAN BERBASIS WEBSITE - Rizki, Muhammad Ainur; Murpratiwi, Santi Ika; Anjarwani, Sri Endang (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2024)
Today, the ease of obtaining medicines for the public has improved significantly thanks to developments in technology and healthcare infrastructure. Access to medicines has become easier through pharmacies. A survey of 35 community members in Lombok, West Nusa Tenggara showed that 85.3% stored medicines without doctor's instructions and needed education on the proper use of medicines. A survey of 23 pharmacists also showed that 95.5% of pharmacists need a drug education platform that makes it easier for them to provide drug education. Departing from the problem of the lack of public understanding of medicines and the need for pharmacists to provide drug education easily, this study aims to design and build an information system, “ObatPedia,” as an educational media about website-based medicines. The method used is Personal Extreme Programming (PXP) because this website will be developed flexibly, quickly, and responsive to change. In this method, some stages are passed, including Planning, Iteration, Initialization, Design, Implementation, and Testing, so the website can be developed with the expected features and usability. The results Mean opinion score of this system a Mean Opinion score of 4.345 from the public and 4.472 from pharmacists on a scale of 1 to 5, which shows that users strongly agree that the ObatPedia website can help to increase public knowledge and understanding of medicines.